A configurational evaluation of elite sport policy in South Africa: A realist perspective - Jacobs, S. D. (Stellenbosch University, Vrije Universiteit Brussel, 2019)
Over the years, the attainment of international sporting success has become a critical important focus of the South African government. In this regard, specific elite sport policies have been introduced by policymakers in order to ensure that sport persons can perform internationally. Elite sport policies and the implementation thereof have been identified to be quite complex in reality, and differ considerably from one country to another. The overall aim of the current study was to assess what facilitates and/or inhibits the elite sport policies of South Africa through the configurational lens of a `realist perspective`, in the case of the Western Cape Province. In this regard, a configuration of several approaches was utilised in the `realist evaluation`. The current study made use of a multi-method research design by involving primary sport stakeholders, namely: athletes; coaches; administrators; expert sport management academics; and government partners. Data was collected and analysed in terms of the `realist perspective` configurational elements, which comprise the components of context and mechanism in order to provide a basis for the outcome elements. The influence of various macro-level contextual factors was examined through the lens of systems theory. This was executed to determine how and to what extent contextual factors may or may not influence an elite sporting system in a nation characterised as an "emerging country". Furthermore, the effectiveness of the elite sport policies was measured using a multidimensional approach (input-throughput-output and feedback cycles). Furthermore, the emerging issues concerning the inter-organisational relationships between government stakeholders were explored by means of juxtaposing two theoretical frameworks, specifically the resource dependency theory and the inter-organisational theory. Research on inter-organisational relationships aided in the understanding on why dyadic government partnerships are formed, how they are managed, what the outcomes are, and how financial resources play a role in the dynamics of these relationships in the current study. The current study on elite South African sport policies produced the following results: (1) the organisation of sport in the country is quite complex; (2) ineffectiveness was established for the sporting performance (output), input and throughput cycles in the Western Cape Province; (3) the nation-specific context was identified to influence the elite sporting system quite extensively; and (4) the inter-organisational relationships between government stakeholders were reported to be challenging due to the variety of barriers that were identified. Firstly, the current study implemented a configurational assessment of the elite sport policies of South Africa, specifically in the Western Cape Province, herewith advancing the field of sport management by adding to the limited number of available studies on elite sport policies of `emerging` countries. Secondly, this study should provide empirical evidence for when policymakers review the (elite) sport policies of South Africa.